Biomechanical Assessment of Reaching Movements in Post-Stroke Patients During a Robot-Aided Rehabilitation. Issue 1 (2nd May 2011) - Mazzoleni, S.; Posteraro, F.; Filippi, M.; Forte, F.; Micera, S.; Dario, P.; Carrozza, M. C.
Abstract : The main goal of this paper is to describe a method for the assessment of the motor performance in post-stroke subjects who have been undergone a robot-aided upper limb rehabilitation treatment. The motivation for adopting such methodology relies on the need of quantitative methods for the evaluation of the effects of robot-aided rehabilitation treatments, which assumes great importance from the clinical point of view. The method is based on the analysis of biomechanical parameters computed from force data recorded during the execution of planar reaching movements. Data from 17 chronic post-stroke patients and 5 healthy subjects were analysed. The results show the effectiveness of the proposed method, which can contribute to quantitatively evaluate the effects of a robot-mediated therapy on the upper limb of chronic post-stroke subjects.